2015
DOI: 10.1016/j.ejvs.2015.06.116
|View full text |Cite
|
Sign up to set email alerts
|

Is Inferior Mesenteric Artery Embolization Indicated Prior to Endovascular Repair of Abdominal Aortic Aneurysm?

Abstract: Type II endoleak is a common condition occurring after endovascular repair of abdominal aortic aneurysms (EVAR), and may result in aneurysm sac growth and/or rupture in a small number of patients. A prophylactic strategy of inferior mesenteric artery (IMA) embolization before EVAR has been advocated, however, the benefits of this strategy are controversial. A clinical vignette allows the authors to summarize the available data about this issue and discuss the possible benefits and risks of prophylactic IMA emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…118e120 Even if preventive interventions have been shown to cause a reduction in the incidence of T2ELs, whether the decreased rate of T2ELs actually translates in clinical benefits remains controversial. 121e123 Indeed, even after successful IMA embolization 124,125 or in patients with chronic occluded IMA, 126 T2ELs can still develop from LAs and result in sac enlargement. Also, more aggressive approaches may cause overtreatment in those patients who will never develop T2EL-related complications, can delay the time to definitive AAA management, and the cost-effectiveness has not been definitely demonstrated.…”
Section: Preventionmentioning
confidence: 99%
“…118e120 Even if preventive interventions have been shown to cause a reduction in the incidence of T2ELs, whether the decreased rate of T2ELs actually translates in clinical benefits remains controversial. 121e123 Indeed, even after successful IMA embolization 124,125 or in patients with chronic occluded IMA, 126 T2ELs can still develop from LAs and result in sac enlargement. Also, more aggressive approaches may cause overtreatment in those patients who will never develop T2EL-related complications, can delay the time to definitive AAA management, and the cost-effectiveness has not been definitely demonstrated.…”
Section: Preventionmentioning
confidence: 99%
“…A recently published meta-analysis reported on the reduction of type II endoleaks. 15 This previous meta-analysis found that IMA embolization is associated with a significantly low risk of type II endoleaks; however, the studies assessed were all retrospective trials. After the completion of the randomized prospective study on this topic that is currently underway, we will have a better understanding of the effectiveness of this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effectiveness of preventive embolization of aortic branches is controversial (51), patients with inferior mesenteric artery diameter > 3.0 mm or lumbar artery diameter > 2.0 mm can be the candidates for undergoing preventive embolization (Fig. 5) (52).…”
Section: Evar Techniquementioning
confidence: 99%